The association of lung ultrasound images with COVID‐19 infection in an emergency room cohort. (1st July 2020) - Bar, S.; Lecourtois, A.; Diouf, M.; Goldberg, E.; Bourbon, C.; Arnaud, E.; Domisse, L.; Dupont, H.; Gosset, P.
Summary: Lung ultrasound could facilitate the triage of patients with suspected COVID‐19 infection admitted to the emergency room. We developed a predictive model for COVID‐19 diagnosis based on lung ultrasound and clinical features. We used ultrasound to image the lung bilaterally at two anterior sites, one and two hands below each clavicle, and a posterolateral site that was the posterior transverse continuation from the lower anterior site. We studied 100 patients, 31 of whom had a COVID‐19 positive reverse transcriptase polymerase chain reaction. A positive test was independently associated with: quick sequential organ failure assessment score ≥1; ≥3 B‐lines at the upper site; consolidation and thickened pleura at the lower site; and thickened pleura line at the posterolateral site. The model discrimination was an area (95%CI) under the receiver operating characteristic curve of 0.82 (0.75–0.90). The characteristics (95%CI) of the model's diagnostic threshold, applied to the population from which it was derived, were: sensitivity, 97% (83–100%); specificity, 62% (50–74%); positive predictive value, 54% (41–98%); and negative predictive value, 98% (88–99%). This model may facilitate triage of patients with suspected COVID‐19 infection admitted to the emergency room.